A Study on the Correlation between Intelligence and Body Schema in Children Who Practice Chess at School - Vlad Ionuț Stegariu; Beatrice Aurelia Abalasei; Marius Stoica (MDPI AG, 2022)
The role of intelligence in chess is crucial because the game involves a situation of adversity between two players whose goal is to checkmate the opponent's king. Due to the complex nature of the game and the huge amount of information needed to become a professional chess player, the ability to receive, analyze, sort and use abstract notions is essential. A total of 67 children from the third grade were selected and tested twice, initially and finally, to establish the level of body schema and intelligence. The Raven test was used to numerically quantify their intelligence and the Goodenough test was conducted for the body schema. We used the paired samples T-test to highlight the statistical difference between the results and performed a simple linear regression to see if the level of intelligence is a predictor of the body schema. There is a linear relationship between intelligence and body schema, and we can use the first one to predict the evolution of the second. In conclusion, body schema can be educated through chess lessons, and this will lead to better psychomotor development.